Implementasi Algoritma AES Untuk Pengamanan Login Dan Data Customer Pada E-Commerce Berbasis Web - Laila Mustika (STMIK Budi Darma, 2020)
In the field of E-Commerce website security is very necessary considering that many cyber crimes target commercial websites. Some that need to be secured are logins, because logins are confidential and important to access a website that has account access rights. In addition, customer data also needs to be secured data from people who do not have access rights, to prevent and avoid data changes and destruction. If customer data is known by parties who do not have access rights, the data can be misused and can lead to fraud cases. Therefore an algorithm is needed to secure the website. One of the algorithms that can be used to secure a website is cryptography. In cryptography messages or important and confidential data are encrypted and described using a symmetric key or asymmetric key that is only known by the authorities. There are several methods of cryptographic algorithm that can be applied to it, one of them is the AES (Advanced Encryption Standard) method. AES algorithm has a block length of 128 bits and is able to support key lengths of 128, 192, and 256bit, besides that AES algorithm is cheaper in cost and more easily implemented in small memory. The results of the application of the AES Algorithm make the website safer and it is hoped that customers will increase with increased website security and customer trust